Level of Knowledge of Pregnant Women about Oral Diseases - Jaime Fernando Armijos Moreta; Silvia Marisol Gavilanez Gavilanez; Freddy Gastón Santillán Molina; Ofelia Cecilia Ramírez Hidalgo (Medisur)
Background: among the main problems that can affect the health of pregnant women are damage to the oral cavity. Objective: to determine the level of information that pregnant women have about oral diseases during pregnancy. Method: an observational, cross-sectional study was carried out in the period from April 1 to June 30, 2022 in the Santo Domingo Canton, Santo Domingo de los Tsáchilas province, Ecuador. The population consisted of 20 pregnant women. The variables studied were: information received on the importance of oral hygiene during pregnancy, frequency of visits to the dentist, educational activities received on oral hygiene, information on the affectations that oral diseases produce in the baby during pregnancy and recognition of the oral health prevention activities during pregnancy. The results were presented in graphs using absolute (numbers) and relative (percentages) frequencies. Results: more than 90 % of the pregnant women stated that they had received information on the importance of oral hygiene during pregnancy, 55 % indicated that they attended the dentist only once during the entire gestation period, 50 % stated that they had never received educational activities on oral hygiene, 55 % of the participants expressed not having information about the effects caused by oral diseases during pregnancy and more than half recognized that oral health prevention activities should be carried out. Conclusions: poor oral hygiene is one of the risks that pregnant women must face. Providing him with an adequate level of information on oral health prevention is vital and necessary for his health and that of the baby.